Hubungan Dukungan Sosial Dengan Tingkat Resiliensi Pada Petugas Kesehatan Selama Masa Pandemi Covid-19 di Puskesmas Kaliabang Tengah - Endang Setia Asih (2021)
The Covid-19 pandemic has had a significant impact on the community, especially for health workers who are at the forefront of providing health services. Therefore, social support is needed to increase resilience during the pandemic. The purpose of this research. This study aims to determine the relationship between social support and the level of resilience of health workers during the Covid-19 pandemic at the Kaliabang Tengah Health Center. Respondents in this study were health workers who worked at the Kaliabang Tengah Health Center with a total of 48 people using the total sampling technique. The results obtained that the majority of social support was moderate (41.7%), and the level of resilience of the majority was moderate (56.3%) and there was a relationship significant relationship between social support and the level of resilience of health workers with a p-value of 0.000 (p<0.05). So it can be concluded that the higher the social support, the higher the resilience level of health workers. It is recommended for health workers to participate in activities in health care facilities and at home to increase social support, especially support from friends.